Estrés y su incidencia el desempeño laboral de los médicos del Subcentro Santa Rosa de la ciudad de Quevedo en el año 2020 - Mejia Rodas, Katherine Dayane (2020)
This research set out to identify stress levels in physicians and their impact on job performance. Today it is recognized that stress is one of the main health problems. The study was carried out in a sub-center of the holy rose of the city of Quevedo, in August 2020. The selected participants were 10, doctors between or men and women who responded to a survey in order to be able to measure their stress levels and see if they have an impact on job performance. It was obtained as a result that there is some degree of stress in the doctors, frequent stressors are work overload, financial problems, intra-family problems, fear of catching the covid 19 virus and of infecting their family. An unmotivated, poorly paid doctor with financial and interpersonal problems tends to be more prone to stress, stress not only affects the doctors but also the patients as they would not be well cared for by the doctor. If it is not assessed in time, it would turn into moderate, severe or extreme chronic stress or burnout syndrome. One of the first symptoms of a mild nature but the list of psychological symptoms goes from mild that are like signs of stress is: difficulty getting out of bed, which means that the body is tired, pathological exhaustion at a moderate level, is the bad mood, frustrated nothing fills him up, incompetence and at severe levels no will to live absenteeism usually abusing drugs drugs and alcohol The doctor was evaluated and strategies for the prevention of work stress were created. They must focus on combating stressors from their source.